IMMIGRANT WELCOMING PROCESS IN THE SUS IN ANÁPOLIS AND IN THE FRENCH HEALTHCARE SYSTEM: A COMPARATIVE STUDY - Andrade, João Pedro Duarte de; Silvestre, Hugo de Andrade; Costa, Mariana Rezende Maranhão da (CIPEEX, 2025)
Immigration is an ancient practice driven by the search for better living conditions, with 281 million immigrants worldwide in 2020, representing 3.6% of the global population. In Goiás, migration began in the 16th century, increased in the 18th century, and stabilized until revitalization during Getúlio Vargas’s "March to the West." Recently, Brazil has seen an increase in Latin American immigrants, especially Haitians and Venezuelans. Comparing healthcare systems, France has a more publicly supportive system, while Brazil faces deterioration in public provision and increased marketization, which hinders immigrant access. Analysis of SUS demands for immigrants in Goiás, compared to the French system, shows that, although access to healthcare is guaranteed, language barriers persist in both countries. In Goiás, the main immigrant groups are Venezuelans (22.8%), Haitians (12.5%), and Portuguese (9.2%). In Anápolis, most immigrants are aged 20–59 years, and 42% are between 0–19 years, with only 8% holding higher education degrees. Health data show that 78.1% have no specific conditions, with low diabetes and hypertension rates. France uses brochures in 23 languages and intercultural mediators; it is recommended that Brazil adopt similar measures and provide better training for healthcare professionals to improve immigrant care. Further research is needed to enhance healthcare delivery in Brazil.